Decreasing hepatitis B seroprevalence in pregnant women in Taiwan between 2016 and 2021: a claim-based cohort study - Li-Nien Chien; Juan C. Vargas-Zambrano; Meng-Yun Ku (BMC Public Health)
Abstract Background Hepatitis B virus (HBV) surface antigen (HBsAg) seroprevalence was high before the national vaccine policy was introduced in Taiwan, indicating significant HBV infection rates. The success of the HBV immunization program and other preventive measures likely led to decreased HBsAg prevalence among pregnant women. This study reports on the HBV seroprevalence among pregnant women in Taiwan from 2016 to 2021, including those potentially affected by the universal hepatitis B vaccination at birth. Methods This claim-based cohort study included pregnant women with hospital-based prenatal HBV screening data: 162,662 for HBsAg and 161,729 for HBeAg, from 2016 to 2021. Patient medical records were reviewed to collect information on demographic characteristics and other health conditions. Logistic regression models were used to identify risk factors associated with HBsAg and HBV e antigen (HBeAg) positivity. Results The seroprevalence for HBsAg and HBeAg during the study period was 4.0% and 0.6%, respectively. HBsAg positivity was highest among women born before July 1984 (pre-vaccination period; 8.6%), decreasing to 2.2% among those born between July 1986 and 1988 (national vaccination implementation) and further declining to 1.1% for those born after 1997. These data underscore the crucial role of large-scale immunization strategies in controlling HBV infections. Similarly, HBeAg positivity was highest among pregnant women born before the vaccination program (~ 1.0%), decreasing significantly to 0.4% for those born after 1989. The results showed geographic variations, potentially reflecting factors such as the mother’s age and foreign nationality. However, the birth year was the most crucial factor associated with HBV marker positivity. Conclusions The implementation of national vaccination programs has demonstrated significant success in reducing HBV seroprevalence among pregnant women, which is particularly evident in the substantial decrease in HBsAg seroprevalence in Taiwan post-July 1986. These findings emphasize the importance of continued and consistent vaccination efforts, supporting the need for ongoing public health strategies to combat HBV infections effectively.